Use of Recycled Potting Medium for Containerized Production of Squash - Marie Dorval; Riphine Mainviel; Vincent Michael; Yuqing Fu; Bala Rathinasabapathi; Geoffrey Meru (EDIS)
Vegetable growers are keen on cost-cutting measures to increase profitability. Containerized vegetable production can be done in a shade-house or garden, and it often requires commercial potting media. Although expensive, potting media are lightweight and provide high water- and nutrient-holding capacities, and thus they are widely used by growers. Growers often discard or compost the potting media after a single season due to issues such as diseases, pests, and weeds. However, old potting media could be reused for containerized production if appropriately sterilized and amended with fertilizer salts. The current study was conducted to determine the feasibility of using sterilized recycled potting medium amended with fertilizer salts for containerized production of squash. This new 4-page publication of the UF/IFAS Horticultural Sciences Department was written by Marie Dorval, Riphine Mainviel, Vincent Michael, Yuqing Fu, Bala Rathinasabapathi, and Geoffrey Meru. https://edis.ifas.ufl.edu/hs1404